S7 Airway Pathological Phenotypes and their Clinical Utility in Adult Asthma. (12th November 2015) - Siddiqui, S; Shikotra, A; Richardson, M; Doran, E; Choy, D; Shelley, M; Hargadon, B; Arron, J; Brightling, C; Heaney, L; Wardlaw, A; Bradding, P
Abstract : Background: Airway remodelling and cellular inflammation are well recognised pathological features of asthma. However the relationship between asthma phenotype, treatment intensity and pathology is poorly understood. Objectives: We performed a study of common pathological features in adult asthmatic bronchial biopsies to identify (i) whether discrete 'pathological phenotypes/subtypes' exist and (ii) their clinical utility. Methods: 202 patients (142 asthma and 60 healthy volunteers) were recruited. Patients underwent bronchoscopy and endobronchial biopsy. Bronchial biopsies were evaluated for eleven common features of asthma pathology. Standard biostatistical analyses including a range of cluster analyses and machine learning were applied to pathological features alone to evaluate our objectives. Results: Three distinct immunopathological clusters were identified and characterised by distinct biopsy features of cellular inflammation and remodelling. Specifically, i) late onset severe eosinophilic asthma [cluster 1] with evidence of reticular basement membrane thickening, increased epithelial area and vascular remodelling, ii) milder late onset asthma [cluster 2] with few features of remodelling and iii), an early onset atopic eosinophilic asthma [cluster 3] with features of Th2 high asthma, increased airway smooth muscle (ASM) mass, increased mast cells within the ASM and a mixed granulocytic submucosal inflammation. Pre bronchodilator FEV1 and decline (in a subset) differed across the clusters. Pathological features did not add value to the clinical prediction of asthma. Conclusion: We have identified three novel pathological clusters of asthma with differing features of airway remodelling, cellular inflammation and airway function. Asthma may be characterised by variable pathological phenotypes warranting further evaluation in larger population studies.